QUALITATIVE STUDY OF CONSUMER PERCEPTION ON RETAILER PRIVATE LOCAL BRAND PRODUCT (CASE STUDY AT ALFAMART AND INDOMARET MINI MARKET IN MANADO) - Sondakh, Harini .; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The continuously growth of business world of retail industry can’t be separate by how consumer react towards their private local brand that’s why the purpose of this study is to analyze consumer perception on Retailer Private Local Brand Product at Alfamart and Indomaret mini market in Manado area. using in-depth interview result show that most of respondents already buy private local brand of Alfamart and Indomaret mini market in Manado area but only certain kind of private local brand product (PLB) like mineral water, dry and wet tissue, under wear for man and woman, lighter, snacks and envelop. There are many more PLB products but only those products that dominantly purchased by consumers. By this, retailer like Alfamart and Indomaret mini market company need to maintain the selling of most purchased PLB products and hold the true identity of PLB product itself and able to compete with other famous brand not just by the price but also the quality of the product with lower and affordable price.Keywords: marketing, private local brand, consumer perception, perceived price, perceived quality, perceived risk, perceived value.